Javanese Literature since Independence - Ras, J. (Brill, 1979)
Indonesia
English
Keywords: Asian history; indonesia; Imset; Jalaran; Javanese traditional house; Kenya; Kudu; Minute and second of arc; Prachuap Khiri Khan; Short story